THE DEVELOPMENT OF THE BANKING SYSTEM IN CONDITIONS OF DESTRUCTIVE IMPACT OF INTERNAL AND EXTERNAL FACTORS - L. Zaburanna; L. Nedilska; I. Abramova; N. Kurovska; G. Martynuk (Наукові горизонти, 2020)
The article presents the substantiation of the methodological model of the development of the banking system of Ukraine. The purpose of the research is to analyze the key aspects of the functioning of the banking system of Ukraine as well as to provide the theoretical and methodological substantiation of the model for its development. The analysis of the issues raised in the study was carried out according to the general methodological scheme of the system approach. The empirical analysis was conducted using the data of 2013–2017. Monetary instruments of the central bank, which allowed an objective evaluation of its activities in the field of monetary regulation, are identified in the course of the research. The main trends in the development of the banking system of Ukraine are revealed. It is established that it was possible to stabilize the situation in the banking system owing to the restoring of the fund base, recognizing the real quality of assets and implementing programs of capitalization by virtually all large banks. It is found out that commercial banks currently own a right amount of capital and liquidity to resume lending to the economy. The most probable trend of the development of the banking system of Ukraine in the immediate future is illustrated. It is established that a clear and realistic paradigm with the outlined priorities, objectives, tasks, and the stages of its implementation is able to ensure a sustainable development of the banking system. The most important tasks for the development of the banking system in accordance with the European integration processes, national needs and interests are defined; they include effective redistribution of capital; high-quality banking services; sufficient level of competitive ability; compliance of the domestic banking system with the international standards; financial availability (inclusion). The implementation stages of the paradigm for the development of the banking system of Ukraine are established, namely restoration, activation and well-balanced international integration.